Development of a microfluidic paper-based analytical device for magnesium determination in saliva samples - Juliana I.S. Aguiar; Mafalda T.S. Silva; Helena A.G. Ferreira; Elisabete C.B. Pinto; Marta W. Vasconcelos; António O.S.S. Rangel; Raquel B.R. Mesquita (Talanta Open, 2022)
In this work, a microfluidic paper-based analytical device (μPAD) was developed for magnesium determination in saliva samples. The idea was to develop a fast and simple method for biological magnesium quantification targeting saliva as an easy to collect and non-invasive alternative to blood or urine samples. The μPAD approach was chosen due to its advantages, namely ideally suited to conduct on-location determinations, and not requiring trained operators or specialized laboratory equipment. The developed μPAD was based on the colorimetric reaction between eriochrome cyanine and magnesium to form an intense orange/reddish colour product. The colour intensity was determined by image processing after digital scanning, made within 10 to 90 min after sample loading. Under optimal conditions, the dynamic concentration range was 82–247 μM, with detection and quantification limits of 62 μM and 81 μM, respectively. The device is stable for up to 3 months when stored in vacuum or in a modified nitrogen atmosphere. An accuracy assessment was made by comparing the results obtained using the developed μPAD with those from atomic absorption spectrometry (AAS). The relative difference between the two sets of results was below 5%.